Competing in Collegiate Championships during COVID: Caveat or Calamity - Pappert, S. K. (University of Denver Sports & Entertainment Law Journal, 2021)
Upon the NCAA`s attempt to resume athletics in the fall semester of 2020, NCAA president Mark Emmert said "Our (NCAA) decisions place emphasis where it belongs — on the health and safety of college athletes." In a world currently battling the COVID-19 pandemic, the idea of athletes travelling across the country and playing sports, especially high intensity ones, is a dangerous combination. Football players know that every time they put on their pads and helmets, they are playing a dangerous game that could kill them, but they did not expect to practice, travel, and compete in such perilous circumstances. One UCLA football player worried that student-athletes` fears will only be recognized when a player finally dies from COVID-19. However, one student-athlete has already died due to COVID-19 complications. Jamain Stephens, a football player for California University of Pennsylvania, a Division II member of the NCAA, passed away due to a blood clot following being diagnosed with COVID-19.